HAYES, Kelly E. Holy Harlots: Femininity, Sexuality and Black Magic in Brazil. Berkeley, CA: University of California Press, 2011. 293pp. ISBN: 9780520262652 - Moura, Mariana Mendes (PLURA, Revista de Estudos de Religião / PLURA, Journal for the Study of Religion, 2016)
<p class="MsoNormal" style="text-align: justify; line-height: 200%; background-image: initial; background-attachment: initial; background-size: initial; background-origin: initial; background-clip: initial; background-position: initial; background-repeat: initial;">Resenha de HAYES, Kelly E. Holy Harlots: Femininity, Sexuality and Black Magic in Brazil. Berkeley, CA: University of California Press, 2011. 293pp. ISBN: 9780520262652